RNase H2 Loss in Murine Astrocytes Results in Cellular Defects Reminiscent of Nucleic Acid-Mediated Autoinflammation - Bartsch, Kareen; Damme, Markus; Regen, Tommy; Becker, Lore; Garrett, Lillian; Hölter, Sabine M; Knittler, Katharina; Borowski, Christopher; Waisman, Ari; Glatzel, Markus; Fuchs, Helmut; Gailus-Durner, Valerie; et al. (Frontiers in Immunology, 2018)
Aicardi–Goutières syndrome (AGS) is a rare early onset childhood encephalopathy caused by persistent neuroinflammation of autoimmune origin. AGS is a genetic disorder and >50% of affected individuals bear hypomorphic mutations in ribonuclease H2 (RNase H2). All available RNase H2 mouse models so far fail to mimic the prominent CNS involvement seen in AGS. To establish a mouse model recapitulating the human disease, we deleted RNase H2 specifically in the brain, the most severely affected organ in AGS. Although RNase H2ΔGFAP mice lacked the nuclease in astrocytes and a majority of neurons, no disease signs were apparent in these animals. We additionally confirmed these results in a second, neuron-specific RNase H2 knockout mouse line. However, when astrocytes were isolated from brains of RNase H2ΔGFAP mice and cultured under mitogenic conditions, they showed signs of DNA damage and premature senescence. Enhanced expression of interferon-stimulated genes (ISGs) represents the most reliable AGS biomarker. Importantly, primary RNase H2ΔGFAP astrocytes displayed significantly increased ISG transcript levels, which we failed to detect in in vivo in brains of RNase H2ΔGFAP mice. Isolated astrocytes primed by DNA damage, including RNase H2-deficiency, exhibited a heightened innate immune response when exposed to bacterial or viral antigens. Taken together, we established a valid cellular AGS model that utilizes the very cell type responsible for disease pathology, the astrocyte, and phenocopies major molecular defects observed in AGS patient cells.